Novel mycorrhizal cheating in a green orchid: Cremastraappendiculata depends on carbon from deadwood through fungal associations. Issue 1 (6th April 2021) - Suetsugu, Kenji; Haraguchi, Takashi F.; Tayasu, Ichiro
Summary: To date, there has been no robust evidence for the exploitation of saprotrophic non‐rhizoctonia fungi by green plants, although some fully mycoheterotrophic orchids are known to exploit them, and mycoheterotrophic evolution has probably occurred through intermediate mixotrophic stages. We investigated the physiological ecology of a fully mycoheterotrophic species Cremastra aphylla and its photosynthetic sister species Cremastra appendiculata, which putatively exploit saprotrophic fungi. Their mycorrhizal partners and ultimate nutritional sources were determined using molecular, stable isotopic, and radiocarbon analysis. Both Cremastra aphylla and Cremastra appendiculata were consistently associated with wood‐decaying Psathyrellaceae. In addition, both species were highly enriched in carbon‐13 ( 13 C) and, to a less degree, in nitrogen‐15 ( 15 N). The δ 13 C and δ 15 N values of Cremastra appendiculata were intermediate between those of Cremastra aphylla and those of autotrophic plants. All Cremastra appendiculata samples and two Cremastra aphylla samples exhibited elevated Δ 14 C values due to the acquisition of carbon fixed in wood during the past decades ( 14 C‐enriched bomb carbon). Our multifaceted evidence indicated that both species obtained carbon from deadwood via saprotrophic fungi. Our findings strongly suggest that mixotrophic relationships associated with wood‐decaying fungi represent a novel evolutionary pathway for full mycoheterotrophy in orchids.